Dexamethasone-induced intrauterine growth restriction modulates expression of placental vascular growth factors and fetal and placental growth. (2nd February 2021) - Arias, A; Schander, J A; Bariani, M V; Correa, F; Domínguez Rubio, A P; Cella, M; Cymeryng, C B; Wolfson, M L; Franchi, A M; Aisemberg, J
Abstract: Prenatal exposure to glucocorticoids (GC) is a central topic of interest in medicine since GCs are essential for the maturation of fetal organs and intrauterine growth. Synthetic glucocorticoids, which are used in obstetric practice, exert beneficial effects on the fetus, but have also been reported to lead to intrauterine growth retardation (IUGR). In this study, a model of growth restriction in mice was established through maternal administration of dexamethasone during late gestation. We hypothesised that GC overexposure may adversely affect placental angiogenesis and fetal and placental growth. Female BALB/c mice were randomly assigned to control or dexamethasone treatment, either left to give birth or euthanised on days 15, 16, 17 and 18 of gestation followed by collection of maternal and fetal tissue. The IUGR rate increased to 100% in the dexamethasone group (8 mg/kg body weight on gestational days 14 and 15) and pups had clinical features of symmetrical IUGR at birth. Dexamethasone administration significantly decreased maternal body weight gain and serum corticosterone levels. Moreover, prenatal dexamethasone treatment not only induced fetal growth retardation but also decreased placental weight. In IUGR placentas, VEGFA protein levels and mRNA expression of VEGF receptors were reduced and NOS activity was lower. Maternal dexamethasone administration also reduced placental expression of the GC receptor, αGR. We demonstrated that maternal dexamethasone administration causes fetal and placental growth restriction. Furthermore, we propose that the growth retardation induced by prenatal GC overexposure may be caused, at least partially, by an altered placental angiogenic profile.